2011
DOI: 10.1667/rr2587.1
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Irradiation Leads to Acute and Persistent Neuroinflammation with Delayed Increases in T-Cell Infiltration and CD11c Expression in C57BL/6 Mouse Brain

Abstract: Radiotherapy is commonly employed to treat cancers of the head and neck and is increasingly used to treat other central nervous system (CNS) disorders. Exceeding the radiation tolerance of normal CNS tissues can result in sequelae contributing to patient morbidity and mortality. Animal studies and clinical experience suggest that neuroinflammation plays a role in the etiology of these effects; however, detailed characterization of this response has been lacking. Therefore, a dose–time investigation of the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 55 publications
4
107
2
4
Order By: Relevance
“…Importantly, we observed a brain-specific increase in IFN-γ + CD4 + T cells, indicating a selective activation of CD4 + T cells in the brain of PD-1H-KO mice. Elimination of PD-1H expression in KO mice is less effective in the absence of radiation treatment, likely because low-dose ionizing radiation of the brain induces localized inflammation and increased infiltration of lymphocytes (16)(17)(18)(19); these effects may be modulated by PD-1H inhibitory function. GL261 induces CD8 + T cell responses upon cancer vaccine treatment (20).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, we observed a brain-specific increase in IFN-γ + CD4 + T cells, indicating a selective activation of CD4 + T cells in the brain of PD-1H-KO mice. Elimination of PD-1H expression in KO mice is less effective in the absence of radiation treatment, likely because low-dose ionizing radiation of the brain induces localized inflammation and increased infiltration of lymphocytes (16)(17)(18)(19); these effects may be modulated by PD-1H inhibitory function. GL261 induces CD8 + T cell responses upon cancer vaccine treatment (20).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, however, VWF PLT chimeric mice expressing VWF only in platelets also showed infarct sizes that were similar to WT mice (79.6 6 8.1 mm 3 ; n 5 16). Because cranial irradiation may induce persistent neuroinflammation in C57BL/6J mouse brain 21,22 we tested lethally irradiated VWF KO mice transplanted with VWF KO MNCs to exclude any potential effect of irradiation on cerebral injury in our model ( Figure 4C). In this separate set of experiments, infarct sizes were still small (18.71 6 4.31 mm 3 ; n 5 7) and comparable with those observed in VWF KO mice (19.43 6 5.49 mm 3 ; n 5 7).…”
Section: Plasma But Not Platelet Vwf Regulates Arterial Thrombus Fomentioning
confidence: 99%
“…Robbins and colleagues demonstrated the importance of MAP kinase pathways in radiation-induced microglial activation and neuroinflammation (Schnegg et al 2012). Moravan et al (2011), York et al (2012, and Morganti et al (2014) found that mouse cranial exposure to γ-rays and protons at doses above 1 Gy elicits persistent elevation of TNF-α, CCL2, T cell infiltration, GFAP, MHC II+, and CD11c+, accompanied by T lymphocyte infiltration and increased numbers of activated microglia. Sweet et al (2014) found persistent (1 -12 months) decreases in ICAM-1 after ≥ 10 cGy whole-body irradiation of mice with 1 GeV/n protons with a pronounced sex difference; specifically, females were sensitive while males were not.…”
Section: Neuroinflammationmentioning
confidence: 99%